STUDY OF IMPLEMENTATION AND GOOD CORPORATE GOVERNANCE INTERNAL CONTROL SYSTEM (Case Study In a Family Firm) - Deny Nitalia Mindrawati; Theresia Dwi Hastuti (Dinamika Akuntansi Keuangan dan Perbankan, 2023)
This research aims to examine the implementation of Good Corporate Governance (GCG) and the implementation of the company's Internal Control System. Data analysis used the positivism philosophy method in a family business company engaged in the manufacturing industry since 1946. Informants were determined by purposive sampling, namely, taken from the top management, middle management, and staff groups. Data analysis techniques in this study used a case study approach through interviews. Research results: GCG implementation is not following best practices by this family business company, and Internal Control System implementation has not become aware by management.